The Influence of Store Atmosphere on Purchasing Decisions and Visitor Satisfaction as an Intervening Variable at Kopi Praja Bintaro, South Tangerang, Banten Province, Indonesia - Filma Festivalia,; RMW Agie Pradipta,; Mira Maharani, (Technium Social Sciences Journal, 2024)
This research aims to determine the effect of store atmosphere on purchasing decisions and visitor satisfaction as an intervening variable at Kopi Praja Bintaro, South Tangerang, Banten Province, Indonesia. This type of research is quantitative descriptive with path analysis using Accidental Sampling; the sample size is 100 respondents. The data collection technique is by distributing questionnaires with a Likert scale of 1 to 5. The research results show: (1) The shop atmosphere has a significant effect on visitor satisfaction; (2) Visitor satisfaction has a significant effect on purchasing decisions; (3) The store atmosphere has a significant effect on purchasing decisions through visitor satisfaction. The atmosphere at Kopi Praja Bintaro South Tangerang creates a positive experience for visitors that is comfortable, friendly, and satisfying. This increases customer satisfaction, builds long-term relationships, and expands the popularity of these places in the local community. It is essential to maintain a friendly and fun atmosphere with staff peering in and giving open feedback to improve the quality of service.